Learning by doing experience of letters in literacy learning: Object based pedagogical approach - Turan, Mehmet (Sila Science, 2011)
General purpose of this study is to execute the instructional process through the letter-teaching materials which are constituted with objects having predominant sounds, in order to enable the students to learn the letters through making and experiencing in the primary education of literacy, concerning teaching the letters. The primary education of literacy has been resumed through 2 dimensional and 3 dimensional materials which are constituted for that purpose. As model of research; This research, which aims the literacy education through 2 and 3 dimensional letter teaching materials for the education of literacy during the 1st grade of the primary school, presents a quality of study of a quasi-experimental type. Population of the study is constituted by the 1st grade students receiving education during 2008-2009 school year in the province of Elazig. The sample of the study, on the other hand, is constituted by 93 students in total who receive education in departments B, C and D of the 1st grade at Evrenpasa Primary School in the province of Elazig. In this study, which contains the education of literacy supported by 2 and 3 dimensional letter teaching materials in the primary education of literacy, it was concluded that the success of students within the working groups which perform the primary education of literacy with 2 dimensional letter teaching materials was higher compared to the literacy success of students within the control groups which are 3 dimensional and which do not use any letter teaching materials.
Keywords: Language; Literacy; Teaching